A genetic variant of the NTCP gene is associated with HBV infection status in a Chinese population. Issue 1 (December 2016) - Yang, Jingmin; Yang, Yuan; Xia, Mingying; Wang, Lianghui; Zhou, Weiping; Yang, Yajun; Jiang, Yueming; Wang, Hongyang; Qian, Ji; Jin, Li; Wang, Xiaofeng
Abstract Background To investigate whether genetic variants of the HBV receptor gene NTCP are associated with HBV infection in the Han Chinese population. Methods We sequenced the entire 23 kb NTCP gene from 111 HBeAg-positive HBsAg carriers (PSE group), 110 HBeAg-negative HBsAg carriers (PS group), and 110 control subjects. Then, we performed association analyses of suggestively significant SNPs with HBV infection in 1075 controls, 1936 PSs and 639 PSEs. Results In total, 109 rare variants (74 novel) and 38 single nucleotide polymorphisms (SNPs, one novel) were screened. Of the seven non-synonymous rare variants, six were singletons and one was a double hit. All three damaging rare singletons presented exclusively in the PSE group. Of the five SNPs validated in all 3650 subjects, the T allele of rs4646287 was significantly decreased (p  = 0.002) in the PS group (10.1 %) and PSE group (8.1 %) compared to the controls (10.9 %) and was decreased to 7.4 % in the PSE hepatocellular carcinoma (HCC) subgroup. Additionally, rs4646287-T was associated with a 0.68-fold (95 %CI  = 0.51–0.89, p  = 0.006) decreased risk of PSE compared with the controls. The NTCP mRNA level was lower in HCC tissues in "CT + TT" carriers than in "CC" carriers. Conclusions We found a genetic variant (rs4646287) located in intron 1 of NTCP that may be associated with increased risk of HBV infection in Han Chinese.